Acoustic wave three-dimensional ground reflection and bouncing. (September 2021) - Serafini, Jacopo; Bernardini, Giovanni; Grignaffini, Giacomo; Modini, Sara; Gennaretti, Massimo
Abstract: This paper deals with the development of a noise propagation tool for the prediction of perceived noise due to aircraft/rotorcraft flying in a non-uniform atmosphere over a non-flat ground. The far-field noise is predicted through a direct ray tracing method, once the near-field aeroacoustic solution, used to define the aircraft/rotorcraft equivalent noise source, is known from a near-field aeroacoustic solver. The atmospheric effects are taken into account in the ray tracing algorithm through standard formulations. A new algorithm capable of taking into account the realistic orography and terrain properties handles the interaction between sound rays and ground. The ground orography is automatically generated by exploiting the open-source Application Programming Interface Open-Elevation, whereas the soil composition is defined using the CORINE Land Cover inventory. The new algorithm, applying the ground absorption on each ray independently and moving the waves interference evaluation to a post-processing space–time interpolation process, allows the inclusion of the contributions of multiple-reflecting rays in the evaluation of the receiver noise. The numerical investigation is aimed at validating the proposed tool against a Fast Field Program solver, as well as at assessing the effects of the realistic description of the terrain on the predictions of perceived noise.